The Role of Islamic Propagation Journalism in the Midst of the COVID-19 Pandemic (Muslim Journalism Continues to Promote Propagation) - Sufkasman, Sufkasman (Jurnal Mercusuar, 2020)
The da’wah journalist continues to broadcast Islam through the writing in the centre of pandemic COVID-19. Journalists at the forefront do not back out trying to find news in the midst of the corona pandemic. Starting from the reporting stage, summarizing and concluding the news through the direct observation process to pulsing information for the public. The role of the da’wah journalist includes the spearhead of the news coverage of pandemic COVID-19. The da’wah journalist was expected to appear over and over again to provide a spiritual backwater against the COVID-19 plague. The da’wah journalists should take an active role to bring peace to the public, to keep the public alert from the deadly virus threats. Journalists in the da’wah are found constantly suggesting public through sparkling information. Advising people to maintain positive thoughts, act positive and be positive, helping the public provide solutions to a dreaded illness during the pandemic COVID-19.